2010
DOI: 10.1111/j.1757-837x.2010.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Fusarium toxins during traditional Turkish maize bread production

Abstract: Introduction The occurrence of major Fusarium toxins in maize samples collected in the Black Sea region of Turkey and fate of these toxins during traditional Turkish maize bread production was investigated. Materials and methods Twenty maize samples were analysed for deoxynivalenol, zearalenone, fumonisins, T-2 and HT-2 toxins. Contamination profiles of maize samples were determined in order to choose the toxins to be monitored during bread production. Breads were produced from low or uncontaminated maize samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The levels of fumonisin contamination in feed, corn, and corn-based products range between 0.25 μg g -1 and 188±25.38 μg g -1 generally in the country (SONAL & ORUÇ, 2000;OMURTAG, 2001;OCAK & BOSTAN, 2010). Analyses in corn fl our conducted in the northern region of Turkey pointed out that processing of corn is critical in the decontamination from Fusarium toxin (NUMANOGLU et al, 2010). However, out of the large number of researches conducted to detect the level of fumonisin in corn and cereals, a few are studied in plants that are used with medicinal and dietary purpose.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of fumonisin contamination in feed, corn, and corn-based products range between 0.25 μg g -1 and 188±25.38 μg g -1 generally in the country (SONAL & ORUÇ, 2000;OMURTAG, 2001;OCAK & BOSTAN, 2010). Analyses in corn fl our conducted in the northern region of Turkey pointed out that processing of corn is critical in the decontamination from Fusarium toxin (NUMANOGLU et al, 2010). However, out of the large number of researches conducted to detect the level of fumonisin in corn and cereals, a few are studied in plants that are used with medicinal and dietary purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Substantial reductions of DON can be achieved (Bartkiene et al , 2008). However, data from other experiments indicated that baking does not reduce DON levels signifi cantly (Creppy, 2002;Numanoglu et al , 2010).…”
Section: Deoxynivalenol (Don)mentioning
confidence: 89%
“…(Castelo et al , 1998) have reported that fumonisins added to cornmeal and present in artifi cially contaminated cornmeal samples were unstable under roasting conditions, but remained fairly stable during canning and baking of corn-based foods, because canned and baked products reached lower temperatures than the roasted products. (Numanoglu et al , 2010) also came to this conclusion because there was no signifi cant reduction of fumonisins in the bread crust and crumb of traditional Turkish maize bread. (Alberts et al , 1990) suggested that FB 1 was found to be stable to heating, as there was no reduction in the FB 1 level after boiling culture material of F. Moniliforme MRC 826 .…”
Section: Fumonisins (Fum)mentioning
confidence: 89%
See 1 more Smart Citation
“…Some of the mycotoxins produced by Fusarium species are generally heat stable and cannot be eliminated by the most commonly employed food-processing techniques, which results in transfer of mycotoxins into beer or other cereal-based food products (Cavret and Lecoeur 2006;Bullerman and Bianchini 2007;Numanoglu et al 2010). These mycotoxins have been detected in various traditional beers (Odhav and Naicker 2002;Nkwe et al 2005;Shephard et al 2005).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%